Protocol paper for the ‘Harnessing resources from the internet to maximise outcomes from GP consultations (HaRI)’ study: a mixed qualitative methods study - Seguin, M; Hall, L; Atherton, H; Barnes, R; Leydon, G; Murray, E; Pope, C; Ziebland, S; Stevenson, F (BMJ Publishing Group, 2018)
Introduction Many patients now turn to the internet as a resource for healthcare information and advice. However, patients’ use of the internet to manage their health has been positioned as a potential source of strain on the doctor–patient relationship in primary care. The current evidence about what happens when internet-derived health information is introduced during consultations has relied on qualitative data derived from interview or questionnaire studies. The ‘Harnessing resources from the internet to maximise outcomes from GP consultations (HaRI)’ study combines questionnaire, interview and video-recorded consultation data to address this issue more fully. Methods and analysis Three data collection methods are employed: preconsultation patient questionnaires, video-recorded consultations between general practitioners (GP) and patients, and semistructured interviews with GPs and patients. We seek to recruit 10 GPs practising in Southeast England. We aim to collect up to 30 patient questionnaires and video-recorded consultations per GP, yielding up to 300. Up to 30 patients (approximately three per participating GP) will be selected for interviews sampled for a wide range of sociodemographic characteristics, and a variety of ways the use of, or information from, the internet was present or absent during their consultation. We will interview all 10 participating GPs about their views of online health information, reflecting on their own usage of online information during consultations and their patients’ references to online health information. Descriptive, conversation and thematic analysis will be used respectively for the patient questionnaires, video-recorded consultations and interviews.